Fato jurídico tributário periódico e os princípios da irretroatividade tributária e da segurança jurídica - Amaral, Keyliane de Sousa (Universidade Federal do Tocantins, 2023)
The present work has for object the analysis of the periodic legal-tax facts, and its relation with the principle of non-retroactivity, foreseen in the art. 150 of the Federal Constitution, from the point of view of the jurisprudence of the Federal Supreme Court. It is noteworthy that the periodic legal-tax facts, also called complex triggering facts, were the object of a lot of divergence in the recent legal system, which was not facilitated by the absence of a more diligent legal treatment by the legislator. In this way, the objective was to analyze the treatment given to the matter, carrying out a conceptual digression to demonstrate the scope of tax principles, and the generating facts, and the way in which the jurisprudence has historically dealt with these cases, and the most recent understanding of the Praetorium Excelso on the matter.